In-orbit assembly mission for the Space Solar Power Station. (December 2016) - Cheng, ZhengAi; Hou, Xinbin; Zhang, Xinghua; Zhou, Lu; Guo, Jifeng; Song, Chunlin
Abstract: The Space Solar Power Station (SSPS) is a large spacecraft that utilizes solar power in space to supply power to an electric grid on Earth. A large symmetrical integrated concept has been proposed by the China Academy of Space Technology (CAST). Considering its large scale, the SSPS requires a modular design and unitized general interfaces that would be assembled in orbit. Facilities system supporting assembly procedures, which include a Reusable Heavy Lift Launch Vehicle, orbital transfer and space robots, is introduced. An integrated assembly scheme utilizing space robots to realize this platform SSPS concept is presented. This paper tried to give a preliminary discussion about the minimized time and energy cost of the assembly mission under best sequence and route This optimized assembly mission planning allows the SSPS to be built in orbit rapidly, effectively and reliably. Highlights: Launch vehicle, orbital transfer and space robots are needed in GEO assembly mission. Assembly procedures for different modules utilizing 2 kinds of robots is presented. Sequence and route planning optimization gives the optimal time and energy cost. Antenna modules cost up to 45% total consumption because weight impacts the most. The planning program is reliable for assembly mission quantitative evaluation.